CORRELATION OF BODY MASS INDEX WITH THYROID-STIMULATING HORMONES IN THYROID PATIENT - Sharma, Anupam; Devi, Savita; Singh, Kamaldeep; Prabhakar, Pranav Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was investigated to determine the correlation of body mass index (BMI) with thyroid-stimulating hormones (TSH) in thyroid patient. Methods: The data which are used in this study were taken in Tagore Hospital and Heart Care Centre (Jalandhar). A total of 90 volunteers both males and females in the age group between 17 and 85 years were included in this study. The following information taken on pro forma such as age in years, height (cm), weight (kg), and history (including: Chief complaints, family thyroid history, blood pressure, temperature, and head and neck examination) from the subjects were collected. Serum T3, T4 and TSH test are performed by the use of instrument ADVIA Centaur@CP Immunoassay System (SIEMENS). The total data were divided into three groups named as: Subclinical hypothyroid (SH) (n=30), euthyroid (n=57), and hyperthyroid including only three patients, and according to age, weight (kg), height (m2), and BMI, the meanÂ±standard deviation (S.D) values were calculated. The BMI is calculated with the formula given by the WHO. Results: For correlation analysis, according to total male and female population in euthyroid group, the mean and SD values of TSH and BMI were calculated. Maximum values of T3 (4.7) and T4 (22.1) in hyperthyroid and TSH (9.9) in SH group were found. The high mean values of T3 (2.92) and T4 (18.46) in hyperthyroid and TSH (29.1) in SH group were observed. Low mean values of T3 (0.97) and T4 (7.7) in SH and low mean TSH (0.04) in hypothyroid group were noticed. Conclusion: Based on the data analysis, it can interpreted that a poor positive correlation between TSH and BMI and poor negative correlation between TSH and BMI are associated in euthyroid subjects. It indicates that, when TSH increases, the BMI will also be increased in total and female euthyroid subjects.